2003
DOI: 10.1002/etc.5620220710
|View full text |Cite
|
Sign up to set email alerts
|

Fish full life‐cycle testing for the weak estrogen 4‐tert‐pentylphenol on medaka (Oryzias latipes)

Abstract: We studied the chronic effects of 4-tert-pentylphenol (4-PP) on reproductive status of medaka (Oryzias latipes) over two generations under continuous exposure, with the goal of verifying the applicability of the fish full life-cycle test (FFLC) for this weak estrogen with this species. The exposure of parental (F0) medaka to 4-PP was begun on embryos within 12 h after fertilization and continued for up to 101 d, with monitoring of embryological development, hatching, posthatch survival, growth, sexual differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Exposures of freshwater fish to EDCs that include an entire life cycle have demonstrated increased sensitivity of subsequent generations measured by fecundity and survival of zebrafish [30], and changes of hepatic vitellogenin and incidence of testisova in medaka [11,31,32]. Multiple-generation exposures of sheepshead minnow to Tb in the present study and to 17b-estradiol [4,5] have demonstrated that in some cases, short-term adult exposures may not effectively predict the impacts on continuously exposed populations.…”
Section: Discussionmentioning
confidence: 53%
“…Exposures of freshwater fish to EDCs that include an entire life cycle have demonstrated increased sensitivity of subsequent generations measured by fecundity and survival of zebrafish [30], and changes of hepatic vitellogenin and incidence of testisova in medaka [11,31,32]. Multiple-generation exposures of sheepshead minnow to Tb in the present study and to 17b-estradiol [4,5] have demonstrated that in some cases, short-term adult exposures may not effectively predict the impacts on continuously exposed populations.…”
Section: Discussionmentioning
confidence: 53%
“…28,2009 accurately determine fish sex. In contrast, GSI and fecundity were unaffected, but fertility was significantly decreased, in female medaka exposed to 4-tert-pentylphenol at 224 mg/L [29]. In general, gross developmental changes in sheepshead minnows, as measured by length and somatic indices, were insensitive and poor indicators of exposure to E2.…”
Section: Discussionmentioning
confidence: 89%
“…Studies have included tributyltin exposures initiated with sheepshead minnow embryos through 30 dph of F1 fish [26], exposure of adult F0 zebrafish (Danio rerio) through 41 dph of the F1 generation to E2 and tamoxifen [27], and exposure of F0 medaka eggs through F1 maturation to the weak xenoestrogens 4-nonylphenol and 4-tert-pentylphenol [28,29]. Studies have included tributyltin exposures initiated with sheepshead minnow embryos through 30 dph of F1 fish [26], exposure of adult F0 zebrafish (Danio rerio) through 41 dph of the F1 generation to E2 and tamoxifen [27], and exposure of F0 medaka eggs through F1 maturation to the weak xenoestrogens 4-nonylphenol and 4-tert-pentylphenol [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…As experimental methods to observe long-term effects, partial life cycle and full life cycle tests have been conducted in order to clarify the effects of chemical compounds over several generations. 11,13,14) It is known that the influence of chemical exposure appears more significantly in juveniles and embryos during developmental stages than in mature parents; thus, several methods, such as exposing fry just after hatching 7,8,[15][16][17] and exposing fertilized eggs, 6,10,11,[16][17][18][19][20] as well as microinjection into fertilized eggs, 21,22) are also utilized. In a special case, artificially inseminated eggs were exposed.…”
Section: Introductionmentioning
confidence: 99%